Foreign Direct Investment: Driving Sustainable Development or Falling Short? - Lapinskaitė Indrė; Stankevych Viktoriia (Economics and Culture)
As countries increasingly rely on foreign direct investment to support economic growth, questions arise about its broader implications for social equity and environmental sustainability. This research aims to investigate the direct and indirect impact of FDI on the sustainable development of developed and developing European countries.